The Material Scope of the Contractual Obligation: The Main Issues of Due Completion and Bona Fide Performance - László Leszkoven (Erdélyi Jogélet, 2024)
The subject of the contract is the service which shall be performed by the debtor for the creditor. The meaning of the terms “shall” and “may require” is rather complex. The service is the true framework institution of the law of obligations (contract law), just as possession is of the rights in rem. The service measures what the debtor is required to provide. And not only the what, when, how much, and where will depend on the proper interpretation of the content and subject matter. The scope also determines the final limit of the effort that can be required of the debtor. In more than one respect, the correct filling in of the content requires serious scientific attention.